Quantitative electromyography: Normative data in paraspinal muscles. Issue 3 (5th July 2020) - Jeppesen, Tina D.; Levison, Lotte; Codeluppi, Luca; Krarup, Christian
Abstract: Background: Quantitative electromyography of paraspinal muscle is a valuable diagnostic tool, but normative data are lacking. Methods: Needle electromyography (EMG) was obtained in 65 healthy subjects (49% men, 51% women) aged 21 to 82 years at C7, Th10, and L5 segments bilaterally. The incidence of spontaneous activity; motor unit potential (MUP) amplitudes, durations, and the incidence of polyphasic potentials; and the recruitment pattern at maximal voluntary contraction (MVC) were evaluated. Results: The incidence of fibrillation potentials was similar to limb muscles. The mean MUP duration and amplitude, and the amplitude at MVC increased caudally, while the incidence of polyphasic potentials was similar at all levels. EMG parameters did not correlate with sex or age. Conclusions: In contrast to limb muscles, EMG parameters did not change with age, while polyphasic potentials were more frequent in paraspinal muscle than in limb muscles. The EMG gradient suggests larger motor units at more caudal segments.